La photocopie et le droit d'auteur au Canada - Nabhan, Victor (Les Cahiers de droit, 1978)
This paper analyses the legal implications of photocopying with regard to the Copyright Act of Canada. Under the law, photocopying is normally illegal, unless it amounts to « fair dealing ». However, this latter exception, at best ambiguous, does not provide a safe shelter under which some of the most common practices could be condoned. In fact, what falls in the scope of the « fair dealing » provision remains a most debatable matter. From these considerations stems the urgency of a change in the law. Parliament should insert a provision delineating in a practical way the sphere of lawful photocopying. On the other hand, copyright owners should be compensated for the use made of their works and collective mechanisms should be created for the recovery of such compensation.